2016
DOI: 10.32607/20758251-2016-8-3-6-16
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Expansion of Hematopoietic Stem and Progenitor Cells from Umbilical Cord Blood

Abstract: Transplantation of umbilical cord blood cells is currently widely used in modern cell therapy. However, the limited number of hematopoietic stem and progenitor cells (HSPCs) and prolonged time of recovery after the transplantation are significant limitations in the use of cord blood. Ex vivo expansion with various cytokine combinations is one of the most common approaches for increasing the number of HSPCs from one cord blood unit. In addition, there are protocols that enable ex vivo amplification of cord bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 113 publications
0
6
0
Order By: Relevance
“…These cytokines have pleiotropic effects linked to stem cell proliferation, mononuclear leukocyte chemotaxis and inflammation; however, one shared feature is that these cytokines target mononuclear leukocytes. SCGF-b triggers proliferative activity of hematopoietic progenitor cells [28] and, together with Flt-3 Ligand and VEGF, it can promote the CD34 + CD133+ progenitors expansion and differentiation into the endothelial cells [29,30]. TNF-β plays a central role in establishing lymphoid microenvironments, host defense and inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…These cytokines have pleiotropic effects linked to stem cell proliferation, mononuclear leukocyte chemotaxis and inflammation; however, one shared feature is that these cytokines target mononuclear leukocytes. SCGF-b triggers proliferative activity of hematopoietic progenitor cells [28] and, together with Flt-3 Ligand and VEGF, it can promote the CD34 + CD133+ progenitors expansion and differentiation into the endothelial cells [29,30]. TNF-β plays a central role in establishing lymphoid microenvironments, host defense and inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…It was suggested that this better support could be attributed to chemokine CXCL12, a critical regulator of hematopoiesis, found to be expressed threefold higher in AT MSC than BM MSC [ 61 , 62 ], even though less than 1% of genes were found to be differentially expressed between AT and BM MSC [ 63 ]. By seeding UCB MNC upon an AT MSC FL and making successive removals of non-adherent cells, Andreeva and colleagues [ 64 ] were able to verify that AT MSC enabled the selection of functionally active CD34 + HSPC at normoxia (20% O 2 ) and hypoxia levels (5% O 2 ) after 7 days of expansion. Even though they used an interesting strategy to enrich CD34 + cells during culture, their expansion levels were quite low (6-10x) compared to our FI of CD34 + cells (60x), which can easily be explained by their lack of exogenous cytokines besides using an expansion system that still relies on FBS usage.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, homing strategies to enhance UCB function include dipeptidyl peptidase 4 inhibition, complement fragment 3a priming, increase in CXCR4 via dimethylprostaglandin E2 pathway, and fucosylation of cell surface molecules required for P-and E-selectin binding. 16,39,40 Successful use of ex vivo expanded UCB requires effective expansion of the hematopoietic progenitor cells as well as stem cells, while maintaining their capacity for homing as well as for short and long-term engraftment. Graft manipulation strategies with UCB focus on these main aspects of CBT and omidubicel has shown the most success with adequate data to support progression to the recent completion of a randomized phase 3 study.…”
Section: Clinical Strategies To Overcome Ucb Cell Dose Limitations An...mentioning
confidence: 99%